Sequential treatment: surgery Radium and cervical cancer stage I and II - Valdivia Ponce, Eduardo (2015)
The authors present their experience with the sequential treatment: Radium and Surgery in 10 cases of cervical cancer in stages I and II. Histopathological studies have shown no residual tumor or lymph node metastases. Morbidity, especially urinary (fistulas), is exactly the same as when surgery alone is used. At present the 10 cases are alive without evidence of disease. Conduct with the possibility of obtaining better results is recommended.